Peran Agen Pelayaran dalam Mendu Peran Agen Pelayaran dalam Mendukung Pencegahan Pencemaran Laut: Studi Kasus di Pelabuhan Teluk Bayur: Peran Agen Pelayaran dalam Mendukung Pencegahan Pencemaran Laut: Studi Kasus di Pelabuhan Teluk Bayur - Sarfini, Medila (Jurnal Cakrawala Bahari, 2025)
Shipping and cargo handling activities at ports have the potential to cause marine pollution, including oil spills, solid waste, and operational residues from ships. This study aims to analyze the role of shipping agents in supporting marine pollution prevention at Teluk Bayur Port, Padang. The research employs a qualitative method with a case study approach to provide a comprehensive understanding of the issue. Data were collected through in-depth interviews with shipping agents, officers from the Port Authority (KSOP), and port operators, as well as through analysis of relevant supporting documents. The findings indicate that shipping agents play three main roles in marine pollution prevention: administrative, coordinative, and educational. Administratively, they are responsible for ensuring that ships comply with environmental standards and international conventions such as MARPOL. Coordinatively, they facilitate communication and cooperation among port stakeholders, including ship owners, operators, and regulatory authorities. Educationally, they contribute to raising awareness among maritime actors about environmentally friendly practices and the importance of pollution prevention. However, the implementation of these roles faces several obstacles, such as limited waste management facilities at the port, weak inter-agency coordination, and insufficient supervision of vessels that do not comply with existing regulations. The study concludes that improving the environmental competence of shipping agents through continuous maritime environmental training, as well as developing standardized operational guidelines for marine pollution prevention at the port level, are essential measures to enhance the effectiveness of pollution control efforts and promote sustainable maritime operations in Indonesia.